Knowledge, Attitude and Practice of Diabetic patients about diabetic retinopathy - Almasoudy, Moaiad Abdullateef; Wahoodi, Zahraa Ali; Mohammed, Israa Adil (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Diabetic retinopathy (DR) is a leading microvascular complication of diabetes mellitus, resulting in progressive retinal damage and vision loss worldwide. Specific Background: Despite the availability of effective screening and treatment options, many patients remain unaware of the risks and preventive measures, particularly in middle-income countries. Knowledge Gap: Limited data exist on the knowledge, attitudes, and practices (KAP) of diabetic patients in Iraq regarding DR, which hinders the development of targeted educational and preventive strategies. Aims: This study aimed to assess the KAP of diabetic patients toward DR at Imam Hassan Center for Diabetes and Endocrinology in Kerbala. Results: Among 368 participants, poor blood sugar control was the most recognized risk factor (59%), while over half (51.1%) were unfamiliar with treatment options. Only 41% believed eye exams were necessary even with controlled blood sugar, and although 83.7% reported regular eye checks, most visits were for spectacle adjustments rather than DR follow-up. Novelty: This is one of the first studies in Iraq to comprehensively evaluate patient KAP toward DR, highlighting systemic gaps in awareness and practice. Implications: Findings underscore the urgent need for structured educational programs and improved screening strategies to enhance patient understanding, promote preventive care, and reduce DR-related vision loss.Highlight : The study highlights limited patient knowledge about diabetic retinopathy. Attitudes toward regular eye exams remain inconsistent among participants. Practices show gaps in routine screening and treatment awareness. Keywords : Diabetic Retinopathy, Knowledge, Attitude, Practice, Diabetic Patients